TOPICAL ISSUES OF HARMONIZATION OF NATIONAL REQUIREMENTS FOR CLASSIFICATION OF DEGREES OF AUDITORS FOR THE CERTIFICATION OF QUALITY MANAGEMENT SYSTEMS WITH INTERNATIONAL - Hlukhova, O. I.; Karandeiev, K. H. (Science and Transport Progress, 2006)
The actual questions of harmonization of national requirements to the public accountants are described.